Parallel implementation of the aeh technique for the solution of plane multiphasic problems - Quintela, Bárbara de Melo (2010)
The Asymptotic Expansion Homogenization (AEH) technique is used to estimate the effective properties of heterogeneous media with periodical microstructure. A considerable computational effort can be necessary even though the adopted models are quite simple. For this reason, parallelization is often necessary to achieve good performance. This work presents a first attempt to parallelize the AEH implementation code. Although the parallelization process is in a very early stage, the preliminary results show that the parallel version provides up to a 30% improvement in application speed. This work consists on a step towards a numerical tool for the analysis of more complex and three-dimensional periodic cells. The two-dimensional AEH was implemented in the C programming language for the future generalization to three-dimensional problems employing the available parallelization tools.